Dampak Ekspansi Kelapa Sawit terhadap Perubahan Ekonomi dan Lingkungan - Amalia Puteri Senaro; Widiyanto Widiyanto; Sandra Sukmaning Adji (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze changes in the structure of community livelihoods and analyze losses from the impact of oil palm expansion on ecology. The research method used is qualitative research, using in-depth interview techniques, observation and documentation. The results of the research show that there is continuity of interaction between society and its economy, which is marked by changes in the structure of the community's livelihood which is now also developing the cultivation of oil palm plantations thereby improving the community's economy, while the sustainability of community interaction with the environment is still visible because the community's environmental ethics still shows an anthropocentristic view of environmental ethics. , The ethic of anthropocentrism causes a decrease in environmental quality and environmental damage in Pelawe Village and Tambangan Village, District. BTS Ulu Cecar, Musi Rawas District in the form of road damage, environmental pollution, land fires and decreased biodiversity. So it can be concluded that the impact of oil palm expansion has a positive impact on the economic dimension and still has a negative impact on the environmental dimension. ​Keywords : Economic, Environmental, Palm Oil Expansion, Human Interaction